School Performance Among a Sample of Type1 Diabetic Children and Adolescents in Erbil City - Bahar Mustafa Aziz, Karwan Hawez Sulaiman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 1 diabetes mellitus (T1DM) is the most common endocrine disorder in children. The glycated haemoglobin (HbA1C) level was found to be correlated with the academic skills and classroom attention in children with T1DM. Left untreated both high and low blood sugar levels can affect the child’s ability to concentrate on schoolwork and participate in school activities. Methodology: In Laila Qasim diabetic center from June to August 2022, a questionnaire survey was used for this cross-sectional study. The sample included 120 diabetic children for case group. All primary and secondary school pupils with type 1 diabetes were included in the study population. Result: In the present study, the correlation between diabetes and poor performance is clear in mathematics, english and science. The highest rate of fair followed not pass was found in uncontrolled HbA1c level (greater than 7) in all subjects except kurdish and found that students with type 1 diabetes had significantly lower overall academic grades than their nondiabetic classmates. Conclusion: Diabetes is associated with reduced neuronal function, which ultimately results in cognitive impairment in areas such as intelligence, learning, memory, information processing, attention, executive function, visual motor integration, and academic performances. Keywords: Type 1 diabetes mellitus; Children and adolescents; Academic performance; School